Joseph Conrad na kartach kwartalnika „Verbum” - Zabierowski, Stefan (Colloquia Litteraria, 2022)
This article presents 2 valuable Polish texts on Conrad, published in Polish Catholic guarterly review „Verbum”. First article,by Rafał Marceli Bluth, presents important event in Conrad`s biography – his decision to leave his native country – Poland for ever. The second article,,by Konrad Górski, offers original interpretation of famous Conrad`s novel – Lord Jim.